The Qur'ān in Italian: An Annotated Chronology - Branca, Paolo (Annali di scienze religiose, 2024)
The very choice to translate a classic or even sacred text of a different religious community, the moment in which the version is produced and the manner in which it is carried out, as well as the apparatuses such as introductions and notes, raise multiple issues at various levels, which are not only linguistic and stylistic, but also cultural and content-related. While restricting the field to the Italian translations of the Qur'an, we will be able to spotlight the different historical contexts and periods in which they appeared and the ever new challenges that translators had to face in an effort that by its very nature can never be considered definitive, but will return to propose itself in different situations, also and perhaps especially in terms of the intentions and purposes that will gradually take over from previous attempts.